1983
DOI: 10.4141/cjps83-114
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Protein Degradation During Wilting and Ensiling of Six Forage Species

Abstract: In the second cut samples, the SNPN content before wilting was significantly higher than that of the first cut (Table 4).Less proteolvsis (increase in SNPN be-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 10 publications
3
71
0
Order By: Relevance
“…Mixing clover and lucerne extracts substantially decreases proteolysis, whereas mixing lucerne extract with boiled clover extract yields a slightly more rapid free amino acid release than lucerne alone [9]. The lower non protein nitrogen that has been found consistently in red clover silage [2,42], results from the action of polyphenol oxidase. This enzyme system reacts with O 2 and phenols normally present in red clover to produce quinones that inhibit the plant proteases that break down forage proteins in the silo [2,11,22,29,50].…”
Section: Discussionmentioning
confidence: 99%
“…Mixing clover and lucerne extracts substantially decreases proteolysis, whereas mixing lucerne extract with boiled clover extract yields a slightly more rapid free amino acid release than lucerne alone [9]. The lower non protein nitrogen that has been found consistently in red clover silage [2,42], results from the action of polyphenol oxidase. This enzyme system reacts with O 2 and phenols normally present in red clover to produce quinones that inhibit the plant proteases that break down forage proteins in the silo [2,11,22,29,50].…”
Section: Discussionmentioning
confidence: 99%
“…In that year, NPN increased by 5% in red clover and 11% in alfalfa wilted under 0% shade, even though less than 5 h was required to reach the desired DM. Papadopoulos and McKersie (1983) found that rapid initiation of proteolysis during a 6-h wilting period resulted in a 7 and 33% increase in NPN in second-growth red clover and alfalfa, respectively.…”
Section: Nonprotein Nitrogen In Wilted and Ensiled Foragementioning
confidence: 99%
“…Red clover (Trifolium pratense L.) and cicer milkvetch (Astragalus cicer L.) consistently underwent less protein degradation than alfalfa (Medicago sativa L.) during ensiling, although neither of these species contains measurable levels of tannins. Other researchers have also found that the increase in NPN during ensiling is much less extensive in red clover than in alfalfa (Papadopoulos and McKersie 1983;McKersie 1985;Jones et al 1995b). Among nine legumes tested by Jones et al (1995a), red clover was the only species with measurable levels of soluble PPO activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the technology of bale silage production, conducted to date, have focused on the effect of herbage wilting and chemical additives on the rate of fermentation, aerobic stability and microbiological quality of silage. The effect of wilting on nitrogen fractions and amino acids in forages has been analyzed under laboratory conditions (PaPadoPouLos, mckersie 1983, meesman et al 1994, Guo et al 2008). caVaLLarin et al (2005 investigated the effect of wilting in the field on the composition of nitrogen fractions and amino acid profile of sainfoin.…”
Section: Introductionmentioning
confidence: 99%